2012
DOI: 10.1073/pnas.1206792109
|View full text |Cite
|
Sign up to set email alerts
|

Development of white matter and reading skills

Abstract: White matter tissue properties are highly correlated with reading proficiency; we would like to have a model that relates the dynamics of an individual's white matter development to their acquisition of skilled reading. The development of cerebral white matter involves multiple biological processes, and the balance between these processes differs between individuals. Cross-sectional measures of white matter mask the interplay between these processes and their connection to an individual's cognitive development… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

40
372
4
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 329 publications
(418 citation statements)
references
References 70 publications
40
372
4
2
Order By: Relevance
“…The observed differences in volume development between good and poor readers might be due to interindividual differences in the coordination of pruning and growth processes (cf. Yeatman, Dougherty, Ben-Shachar, & Wandell, 2012). Although in better readers, pruning might be more prominent and result in the faster formation of more mature and efficient neural reading circuits, growth processes might dominate development in the poor readers resulting in more diffuse cortical representations.…”
Section: Discussionmentioning
confidence: 99%
“…The observed differences in volume development between good and poor readers might be due to interindividual differences in the coordination of pruning and growth processes (cf. Yeatman, Dougherty, Ben-Shachar, & Wandell, 2012). Although in better readers, pruning might be more prominent and result in the faster formation of more mature and efficient neural reading circuits, growth processes might dominate development in the poor readers resulting in more diffuse cortical representations.…”
Section: Discussionmentioning
confidence: 99%
“…FA of the entire left arcuate fasciculus also correlates with phonological awareness in school-age children [36], and the volume of the left arcuate fasciculus correlates with phonological awareness in kindergarteners [45]. Furthermore, in a sample of 58 children between ages 5-9, white matter volume changes within the left arcuate fasciculus predict reading outcomes during the developmental period when children become fluent readers [46]. Similarly, the volume of the left arcuate fasciculus and superior corona radiata assessed in 38 children between five-and six-years predicted third grade reading abilities [47].…”
Section: The Role Of the Arcuate Fasciculus In Reading And Developmenmentioning
confidence: 99%
“…However, the relationship between the developmental trajectory of white-matter tracts and reading acquisition/refinement/ maintenance is yet to be established, and that is the focus of the current study. Here we are defining reading acquisition as the age range of 3-6 years, whereas refinement would include ages from 6 to 14 years and maintenance from ages 14 to 21 years.Longitudinal and cross-sectional studies that assess white-matter maturation and reading development have shed some light on the dynamic relationship between these variables [10][11][12]. Yeatman et al [12] reported that the development of the left arcuate fasciculus (AF; dorsal) and inferior longitudinal fasciculus (ILF; ventral) were related to positive reading gains in children from ages 7 to 15 years and Myers et al [10] extended such findings to include children from kindergarten to grade 3.…”
mentioning
confidence: 95%
“…For example, Takeuchi et al [11] performed longitudinal and cross-sectional studies in children and adolescents and reported a positive relationship between reading and FA in the left dorsal (i.e., AF) and ventral (i.e., inferior fronto-occipital fasciculus [IFO] and ILF) tracts. While these studies have showcased the structural basis of white-matter development for reading, there is still much uncertainty about the dynamic nature of this brain-behavior relationship past the initial reading acquisition stage, despite the evidence of white-matter development through adolescence [12]. In addition, it is important to consider white-matter integrity at distinct developmental stages of reading (i.e., acquisition, refinement, maintenance) as each of these stages requires different skills.…”
mentioning
confidence: 99%
See 1 more Smart Citation